2022
DOI: 10.1021/acs.cgd.1c01320
|View full text |Cite
|
Sign up to set email alerts
|

Semipolar (11–22) AlN Grown on m-Plane Sapphire by Flow-Rate Modulation Epitaxy for Vacuum-Ultraviolet Photodetection

Abstract: Semipolar (11–22) AlN films grown on m-plane sapphire are investigated by flow-rate modulation epitaxy (FME). The full width of half maximums (FWHMs) of thin AlN film for X-ray rocking curves (XRCs) are reduced from 1398 arcsec for traditional growth to 865 arcsec for III-FME. The reduced defect density is attributed to prolonged Al mobility, which results in the transition of growth mode from quasi three-dimensional to two-dimensional step flow. On-axis FWHM[11–23] and off-axis FWHM[0002] of XRCs for 6 μm-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The root-mean-square (RMS) roughness of samples A′, B′, and C′ are measured as 4.91 nm, 2.99 nm, and 2.19 nm, respectively. It can be found that AlGaN samples B′ and C′ have typical undulated surface morphology, which can be explained by the increased anisotropic diffusion lengths of group III atoms and in-plane residual strain on the semipolar (112̅2) surface. , …”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The root-mean-square (RMS) roughness of samples A′, B′, and C′ are measured as 4.91 nm, 2.99 nm, and 2.19 nm, respectively. It can be found that AlGaN samples B′ and C′ have typical undulated surface morphology, which can be explained by the increased anisotropic diffusion lengths of group III atoms and in-plane residual strain on the semipolar (112̅2) surface. , …”
Section: Results and Discussionmentioning
confidence: 98%
“…It can be found that AlGaN samples B′ and C′ have typical undulated surface morphology, which can be explained by the increased anisotropic diffusion lengths of group III atoms and in-plane residual strain on the semipolar (112̅ 2) surface. 24,25 It can be concluded that the improvement of the crystal quality of AlN template is helpful to obtain a high quality AlGaN epitaxial layer, according to the reflectance curves and the surface morphologies. These are consistent with the results previously reported by other researchers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The R of REG-AlN PD and DG-AlN PD are 2.23 and 1.33 A/W at 20 V, respectively, which are superior to the previous performance of VUV PD. 26,27 The external quantum efficiencies (EQEs) of REG-AlN PD are up to 25.3% at 10 V and 1 × 10 3 % at 20 V, respectively. From Figure 6c, it can be seen that the PDs have good repeatability in multiple optical on/off tests.…”
Section: Resultsmentioning
confidence: 99%
“…The dislocations of the semipolar AlN film along the [112̅3̅] AlN direction are mostly connected with F-S partial dislocations. The dislocations along the [11̅00] AlN direction are associated with the F-S partial dislocations, BSFs, and PSFs. ,, The FWHM (0002) of the off-axis was also measured to compare the crystal defects, which is associated with partial dislocations and/or perfect dislocations Figure a,b shows typical XRCs of semipolar (112̅2) AlN epitaxial films grown on m-plane sapphire before and after HTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation